Implementation & simulation of fault locating algorithm and localization for linear transmission lines on PMU based two terminal system. (International Journal of Scientific Research and Management (IJSRM), 2022)
The demand of electricity is increasing rapidly. Among all, electricity is most reliable and sustainable source. With the growth in demand, power system will be more complex and sophisticated. Transmission lines are backbone for supplying electricity to every consumer. Transmission line are mostly prone to faults. So, clearing the fault of transmission in least possible time is most important to reduce the damage occurred due to fault. The protection of the transmission line could benefit tremendously from the capacity to locate and identify the issue. The Phasor Measurement Unit is used in this work to offer a contemporary method of fault localization and detection. The PMU transmission line and fault have been modelled using MATLAB/Simulink. The detection of fault uses discrete wavelet transform, PMU uses discrete Fourier transform and the localization of fault is done using Universal algorithm. In general, this paper provides the concept of PMU and its application in fault detection and locating the fault point in transmission as well as distribution line. The approach taken in this paper has been tested for different line length, source impedance and different types of faults.